The value of 3D images in the aesthetic evaluation of breast cancer conservative treatment. Results from a prospective multicentric clinical trial. (October 2018) - ,; ,; Gouveia, Pedro; Keshtgar, Mohammed; Mosahebi, Ash; Bishop, David; Lacher, René; Liefers, Gerrit Jan; Molenkamp, Barbara; Van de Velde, Cornelius; Azevedo, Isabel; Canny, Rebecca; et al.
Abstract: Purpose: BCCT.core (B reastC ancerC onservativeT reatment.co smeticre sults) is a software created for the objective evaluation of aesthetic result of breast cancer conservative treatment using a single patient frontal photography. The lack of volume information has been one criticism, as the use of 3D information might improve accuracy in aesthetic evaluation. In this study, we have evaluated the added value of 3D information to two methods of aesthetic evaluation: a panel of experts; and an augmented version of the computational model - BCCT.core3d. Material and methods: Within the scope of EU Seventh Framework Programme Project PICTURE, 2D and 3D images from 106 patients from three clinical centres were evaluated by a panel of 17 experts and the BCCT.core. Agreement between all methods was calculated using the kappa (K) and weighted kappa (wK) statistics. Results: Subjective agreement between 2D and 3D individual evaluation was fair to moderate. The agreement between the expert classification and the BCCT.core software with both 2D and 3D features was also fair to moderate. Conclusions: The inclusion of 3D images did not add significant information to the aesthetic evaluation either by the panel or the software. Evaluation of aesthetic outcome can be performed using of the BCCT.core software, with a single frontal image.